Answer:
A. (125.6 in)
Step-by-step explanation:
R = d / 2 = 40 / 2 = 20 in
Circumference is:
S = 2*π*R=2*3.14*20=125.6 in
Let the width be x.
Length is 8 feet more than width. Length = x + 8
Area = x(x + 8)
width increased by 4, that is, (x + 4)
Length decreased by 5, (x + 8 - 5) = (x + 3)
Area = (x + 4)(x +3)
Area remains the same
x(x + 8) = (x+4)(x +3)
x² + 8x = x(x +3) + 4(x +3)
x² + 8x = x² +3x + 4x +12
x² + 8x = x² +7x +12 Eliminate x² from both sides
8x = 7x + 12
8x - 7x = 12
x = 12
Dimensions of original rectangle : x, x + 8
12, 12 +8 = 12, 20
Original rectangle is 20 feet by 12 feet
Answer:
straight line ,
Step-by-step explanation:
because you can see that the line is straight ,
The total cost for a 6-month plan for n lines is represented by the equation:
Cost = 660n + 100
This equation is in the slope intercept form. The coefficient of n represents the slope here.
In the given scenario the slope can be interpreted as the total variable cost for one line for a period of 6 months.
The variable costs are associated with a line are:
1) Unlimited data cost ($40 per month). So for 6 months this cost will be $240
2) Unlimited Call cost ($10 per month). So for 6 months this cost will be $60
3) Unlimited Text Message Cost ($10 per month). For 6 months this cost will be $60.
4) Cost of Phone ($300 per line)
Adding these costs up we get: 240 + 60 + 60 + 300 = $660
Thus, 660 represents the total cost per line for unlimited data, calls, text message and one phone for 6 months. Therefore, option A gives the correct answer.
Answer:
a= -2 and b=3
Step-by-step explanation:
Step 1) Solve the first equation for a:
a + 3b = 7
a + 3b - 3b = 7 - 3b
a + 0 = 7 - 3b
a = 7 - 3b
Step 2) Substitute(7 - 3b) for a in a second equation and solve for b:
2a = b - 7 becomes:
2(7 - 3b) = b-7
(2 multi.7) - (2 multi.3b)= b-7
14 - 6b = b - 7
14 + 7 - 6b + 6b = b + 6b = b + 6b - 7 +7
21 - 0 = 1b + 6b - 0
21=(1 + 6)b
21 = 7b
21
/7 = 7b/7
3 = 7b/7
3 = b
b = 3
Step 3) Substitute 3 for b in the solution to the first equation at the end of Step 1 and calculate a
:
a = 7 - 3b becomes:
a = 7 − (
3 ⋅ 3)
a = 7 −
9
a = −
2